GC-MS STUDY OF THE REMOVAL OF DISSOLVED AND COLLOIDAL SUBSTANCES IN RECYCLED PAPERMAKING BY FLOCCULATION WITH NANO-SIZE TIO2 COLLOIDS - Xiaoquan Chen; Wenhao Shen; Huanbin Liu; Shunli Kou (BioResources, 2011)
In the papermaking process, the removal and control of dissolved and colloidal substances (DCS) is a key issue for reducing the usage of fresh water. Nano-size TiO2 is an excellent capturing and flocculating agent for DCS due to its large surface area and positive charge. The composition of dissolved and colloidal substances in a system and the removal of these substances by flocculation with nano-size TiO2 colloids were determined by gas chromatography and mass spectrometry (GC-MS). The samples were obtained from non-deinked pulp (non-DIP), deinked pulp (DIP), and whitewater. The research results indicated that the removal efficiencies of the DCS, which are associated with the molecular structures, were sequenced from large to small as follows: resin acids and sterols, benzene derivatives containing carboxyl, fatty acids, and the phthalic acid esters. Then, the mechanism of flocculation removal of DCS was considered. With hydrogen bonding between the surface hydroxyl (Ti4+-OH) and the functional groups containing oxygen, the nano-size TiO2 particles can capture dissolved substances (DS), and bridge colloidal substances (CS) and complexes to induce agglomerate flocculation. The flocculating removal efficiencies were influenced by the functional groups and alkyls of the DCS. Greater numbers and polarities of functional groups produced higher removal efficiencies. Long alkyl chains shield functional groups, thereby inhibiting the formation of hydrogen bonding, which results in a decrease in removal efficiencies.